INTERNET BLOCKING: COPYRIGHT INFRINGEMENTS VS. ON-LINE GAMBLING - Pakutinskas, Paulius (European Scientific Journal, ESJ, 2013)
By analyzing the decision of the Court of Justice made on the case of Scarlet Extended SA v Société belge des auteurs, compositeurs et éditeurs SCRL (SABAM), intervening parties: Belgian Entertainment Association Video ASBL (BEA Video), Belgian Entertainment Association Music ASBL (BEA Music), Internet Service Provider Association ASBL (ISPA)1, the article seeks to purify the norms and principles of the primary and secondary EU Law that could be applied not only for the control of Copyright infringements, but also blocking online gambling. Considering the fact that online gambling is spreading worldwide very fast and there is no common specific EU regulation, wider understanding of the filtering problem and assessment of legal problems generated by this problem is important not only theoretically, but also in preparing legal acts.